2014
DOI: 10.1186/s13012-014-0095-y
|View full text |Cite
|
Sign up to set email alerts
|

Implementing the NICE osteoarthritis guidelines: a mixed methods study and cluster randomised trial of a model osteoarthritis consultation in primary care - the Management of OsteoArthritis In Consultations (MOSAICS) study protocol

Abstract: BackgroundThere is as yet no evidence on the feasibility of implementing recommendations from the National Institute of Health and Care Excellence (NICE) osteoarthritis (OA) guidelines in primary care, or of the effect these recommendations have on the condition. The primary aim of this study is to determine the clinical and cost effectiveness of a model OA consultation (MOAC), implementing the core recommendations from the NICE OA guidelines in primary care. Secondary aims are to investigate the impact, feasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
92
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(96 citation statements)
references
References 54 publications
1
92
0
3
Order By: Relevance
“…Ten potential general practices (GPs), who fulfilled the eligibility criteria (see protocol, Dziedzic et al, 2014), were identified through the English West Midlands North and North West Primary Care Research Networks. The practices were introduced to the trial by the study research team at a "roadshow" meeting where they were given information about the study rationale and an overview of its design, the main research questions, what was required from their teams, potential benefits of participation and details of remuneration for clinical time.…”
mentioning
confidence: 99%
“…Ten potential general practices (GPs), who fulfilled the eligibility criteria (see protocol, Dziedzic et al, 2014), were identified through the English West Midlands North and North West Primary Care Research Networks. The practices were introduced to the trial by the study research team at a "roadshow" meeting where they were given information about the study rationale and an overview of its design, the main research questions, what was required from their teams, potential benefits of participation and details of remuneration for clinical time.…”
mentioning
confidence: 99%
“…The care coordinator should conduct a thorough needs analysis, including a standardised assessment of pain and functional disability, in order to be an active and decision-making member of the model 61. From the patient’s clinical profile, the priority symptoms will be targeted in order to obtain a patient-specific model of care 62. As the patient’s expectations evolve with the progression of the disease, the care coordinator will have to perform a thorough reassessment and carry out regular evaluations at appropriate follow-ups.…”
Section: Discussionmentioning
confidence: 99%
“…Randomisation was by practice, so the sample size calculation was inflated to correct for an intracluster correlation coefficient (ICC) (adjusted ICC of 0.005). Varying practice size recruitment was taken into account (including coefficient of variation of 0.5) 131 and included (× 0.67 and × 1.25, respectively for intervention and control practices) adjustments for repeated-measures design.…”
Section: Process Outcomesmentioning
confidence: 99%